Effects of Biological Fertilizer and NPK on Red Chili Growth in Automated Drip Irrigation Systems - Ramdan, Adam Wafi; Aisyah, Aisyah; Sugeru, Herik; Asnur, Paranita; Fahnum, Budi Utami (Jurnal Biologi Tropis, 2025)
Red chili (Capsicum annuum L.) is crucial for household consumption and the food industry, but its productivity declines due to soil fertility depletion caused by excessive chemical fertilizer use. This study aims to evaluate the effects of combining biological fertilizer and NPK on the growth and yield of red chili plants. A factorial completely randomized design (CRD) experiment with 12 treatment combinations was conducted at the UG Technopark Greenhouse, Cianjur, West Java, from May to August 2023. The first factor was the frequency of biological fertilizer application (none, biweekly, weekly, and twice a week), while the second factor was the NPK fertilizer dosage (none, 50%, and 100% of the recommended dose). The results showed that both fertilizers significantly influenced plant growth and yield, with the optimal treatment being the application of biological fertilizer twice a week combined with 100% of the recommended NPK dosage. A significant interaction between NPK dosage and biological fertilizer frequency was observed, affecting plant performance. These findings highlight the importance of integrating biological fertilizers with NPK to enhance red chili productivity while reducing reliance on chemical inputs, contributing to more sustainable agricultural practices.